Implementasi Kebijakan Penyelenggaraan Laboratorium Kesehatan Masyarakat Tingkat 1 pada Integrasi Layanan Kesehatan Primer Di Kota Pekalongan - Imanul Abdi; Antono Surjoputro; Sutopo Patria Jati (Universitas Malahayati, 2026)
ABSTRACT A Public Health Laboratory (Labkesmas) is a health laboratory that provides clinical specimen examination and sample testing services to support disease prevention and control efforts and improve public health, adhering to WHO standards. This research is motivated by the importance of laboratory service requirements in the integration of primary health care services, where community health center laboratories serve as Level 1 Labkesmas in Pekalongan City. This study aims to analyze the implementation of the Level 1 Labkesmas implementation policy in Pekalongan City. Grindle's (1980) policy model theory is used as a research framework to assess the extent of implementation of the Level 1 Labkesmas implementation policy in Pekalongan City. This research method used a qualitative approach through in-depth interviews with respondents representing those who were